Pharmacokinetics and Anti-Diabetic Studies of Gliclazide Nanosuspension - Sunitha Sampathi; Shubham Prajapati; Vijayabhaskarreddy Junnuthula; Sathish Dyawanapelly (MDPI AG, 2022)
Gliclazide (GCZ), an antidiabetic medication, has poor solubility and limited oral bioavailability due to substantial first-pass metabolism. Thus, the purpose of the current study was to optimize and formulate a GCZ nanosuspension (NS) employing the antisolvent precipitation technique. A three-factor, three-level Box-Behnken design (BBD) was used to examine the impact of the primary formulation factors (drug concentration, stabilizer, and surfactant %) on particle size. The optimized NS contains 29.6 mg/mL drug, 0.739% lecithin, and 0.216% sodium dodecyl sulfate (SDS). Under scanning microscopy, the topography of NS revealed spherical particles. Furthermore, NS had a much better saturation solubility than the pure material, which resulted in a rapid dissolving rate, which was attributed to the amorphous structure and smaller particle size of the NS particles. Studies on intestinal permeability using the in vitro noneverted intestinal sac gut method (duodenum, jejunum, and ileum) and single-pass intestinal permeability (SPIP) techniques showed that the effective permeability was also increased by more than 3 fold. In the pharmacokinetic study, the Cmax and AUC0-t values of NS were approximately 3.35- and 1.9-fold higher than those of the raw medication and marketed formulation (MF). When compared to plain drug and commercial formulations, the antidiabetic efficacy of NS demonstrated that it had a significant impact on lowering glucose levels.